Biosynthetic approach to combine the first steps of cardenolide formation in Saccharomyces cerevisiae - Rieck, Christoph; Geiger, Daniel; Munkert, Jennifer; Messerschmidt, Katrin; Petersen, Jan; Strasser, Juliane; Meitinger, Nadine; Kreis, Wolfgang (MicrobiologyOpen, 2019)
A yeast expression plasmid was constructed containing a cardenolide biosynthetic module, referred to as CARD II, using the AssemblX toolkit, which enables the assembly of large DNA constructs. The genes cloned into the vector were (a) a Δ5-3β-hydroxysteroid dehydrogenase gene from Digitalis lanata, (b) a steroid Δ5-isomerase gene from Comamonas testosteronii, (c) a mutated steroid-5β-reductase gene from Arabidopsis thaliana, and (d) a steroid 21-hydroxylase gene from Mus musculus. A second plasmid bearing an ADR/ADX fusion gene from Bos taurus was also constructed. A Saccharomyces cerevisiae strain bearing these two plasmids was generated. This strain, termed “CARD II yeast”, was capable of producing 5β-pregnane-3β,21-diol-20-one, a central intermediate in 5β-cardenolide biosynthesis, starting from pregnenolone which was added to the culture medium. Using this approach, five consecutive steps in cardenolide biosynthesis were realized in baker's yeast.
CRIS-Team Scopus Importer:2019-08-30
Keywords: baker's yeast; biosynthesis; cardenolides; pathway engineering; steroids